Peran Profitabilitas dalam Memediasi Kebijakan Dividen: Studi Kasus pada Jakarta Islamic Indeks 70 - Ghofar, Abd.; Pertiwi, Tri Kartika (Universitas Batanghari, 2024)
This study stems from the phenomenon of investment shifting from the real sector to financial Practice with expectations of obtaining returns in the form of dividend policies. The research examines the impact of Leverage, liquidity and profitability as intermediate variables in dividend policy, for issuers listed in the Jakarta Islamic Index (JII 70). Using several purposive sampling criteria, 25 issuers were selected as research samples. Leverage describes the company's ability to settle obligations with debt; companies with high leverage tend to retain earnings rather than distribute dividends. Liquidity reflects the company's ability to meet short-term obligations; liquid issuers tend to distribute dividends. Profitability, measured through Return on Equity (ROE), is expected to mediate the relationship between leverage and liquidity with dividend policy. According to the Trade-Off Theory, the balance between the use of debt and current assets positively impacts profitability, increasing the likelihood of dividend distribution. The research results show that leverage and liquidity have an adverse impact on dividend policy, with liquidity having a beneficial effect but not contributing to profitability, while leverage negatively affects profitability. Profitability does not significantly mediate the relationship between leverage and liquidity with dividend policy. These findings are important for investors and management in understanding the factors impacting dividend policy decisions in the Sharia capital market.